Performance reviews: why does it matter? / Dr. Roziyana Jafri, Dr. Syahida Abd Aziz and Dr. Kardina Kamaruddin - Jafri, Roziyana; Abd Aziz, Syahida; Kamaruddin, Kardina (Universiti Teknologi MARA, Kedah, 2024)
The impact of performance reviews has undergone significant changes over the years. This reflects shifts in management philosophies, organizational culture, and advancements in human resources practices. Performance review, also known as performance evaluation or performance appraisal, is a systematic and structured process used by organizations to evaluate and assess employees’ job performance against predetermined objectives and criteria (Dessler, 2017). Performance reviews typically involve monitoring progress, providing feedback, setting performance goals, and discussing development opportunities (Pulakos & O’Leary, 2011). It is aimed at increasing the employee’s effectiveness and is like holding a mirror to an employee’s performance. Performance reviews are an excellent opportunity to explore the future and discuss career development goals for each employee (Jen, 2023). Career development remains a highly sought-after element that most employees look for in a job. The purpose of performance reviews is twofold, which means an actionable and accurate evaluation of performance (Jen, 2023). It is a major contributor to employee and organizational performance. The usefulness of performance reviews depends on the organizational goals, culture, and desired outcomes of the review process. The selected definition effectively captures the essence of performance reviews as a strategic process that aligns individual performance with organizational goals, drives business results, and supports employee development. Overall, the objective of this article is to underscore the importance of performance reviews in driving organizational success, continuous improvement, fostering employee development, and creating a culture of accountability.